Sterol bioaccessibility in a plant sterol-enriched beverage using the INFOGEST digestion method: Influence of gastric lipase, bile salts and cholesterol esterase. (15th July 2022) - Makran, Mussa; Faubel, Nerea; López-García, Gabriel; Cilla, Antonio; Barberá, Reyes; Alegría, Amparo; Garcia-Llatas, Guadalupe
Highlights: Inclusion of lipidic enzymes provides a more physiological in vitro digestion scenario. Sterols provided by bile salts and pancreatin must be subtracted from digested samples. Increasing concentration of bile salts decreased plant sterol bioaccessibility. Gastric lipase and cholesterol esterase reduced plant sterol bioaccessibility. Cholesterol cannot be quantified when only cholesterol esterase is used. Abstract: This study evaluates the influence of increasing bile salts and the addition of key enzymes of the lipidic metabolism in the INFOGEST digestion method on sterol bioaccessibility from a plant sterol (PS)-enriched beverage. The assayed modifications were increasing concentration of bovine bile salts (10 vs. 17.5 mM), and addition of gastric lipase (GL) (60U/mL), cholesterol esterase (CE) (0.075 or 2U/mL) or both. Compared to the original method (10 mM bile salts without enzymes), the assayed conditions significantly reduced bioaccessibility of individual (from 11.3 to 19.7 to 5.1–16.6%) and total PS (13.7 to 6.9–8.0%), and cholesterol (52.8 to 20.9–26.1%), except only when CE is added not allowing cholesterol quantification. The bioaccessibility achieved when lipolytic enzymes were tested was similar for all sterols. For a more physiological approach to in vivo conditions, incorporation of bile salts (10 mM), GL (60U/mL) and CE (0.075U/mL) to the INFOGEST method is proposed, although it increases the cost compared to the established method.